2023
DOI: 10.1055/a-2029-0694
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroxylative Cyanation of Alcohols Promoted by Triphenyphosphine/1,2-Diiodoethane

Abstract: Described herein is the Ph3P/ICH2CH2I-promoted dehydroxylative cyanation of alcohols. In contrast to previous dehydroxylative cyanation methods, which may suffer from some limitations, such as the use of transition metals or moisture-sensitive Lewis acids, this protocol features convenient operations, mild reaction conditions and the use of cheap and widely available reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…On the basis of the above results and our previous mechanism studies, 10 we propose a plausible reaction mechanism, as shown in Scheme 3. The in situ generated Ph 3 P + I I − from the Ph 3 P/ICH 2 CH 2 I system may directly coordinate with DMF to produce intermediate A .…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…On the basis of the above results and our previous mechanism studies, 10 we propose a plausible reaction mechanism, as shown in Scheme 3. The in situ generated Ph 3 P + I I − from the Ph 3 P/ICH 2 CH 2 I system may directly coordinate with DMF to produce intermediate A .…”
Section: Resultssupporting
confidence: 65%
“…Previously, we have shown that a Ph 3 P/ICH 2 CH 2 I system can effectively activate the hydroxyl group in DMF, allowing for a wide range of dehydroxylative functionalizations, 10 such as halogenation, 10 a fluorination, 10 d and sulfonylation. 10 f In particular, the halogenation protocol was successfully applied to dehydroxylative chlorination in the total synthesis of Clionastatins A and B reported by the Zhang group, an important step that cannot be achieved by commonly used chlorination methods probably due to the complexity of the molecule.…”
Section: Introductionmentioning
confidence: 99%